The Effectiveness Of Academic Resilience Modules (ARM) In Enhancing Academic Resilience And Academic Achievement Among Students At Risk In Three Southernmost Provinces Of Thailand - Tohtayong, Apirak (2018)
The political and economical instability in three southernmost provinces of Thailand has exposed students to at risk learning environment. These students face diversity and hardship in learning English in this particular situation. Therefore, there is a need to support their learning condition with a module that improves both their academic and psychological quality to deal with such challenges and difficulties. This thesis seeks to design Academic Resilience Module (ARM) aimed at promoting academic resilience and academic achievement of students at risk in three Southernmost Provinces of Thailand. Specifically, it focused on the way to improve the academic resilience and academic achievement in English subject of first year secondary school students.